Combined inhibition of PLCγ-1 and c-Src abrogates Epidermal Growth Factor Receptor-mediated head and neck squamous cell carcinoma invasion - Nozawa, Hiroshi (2008)
PURPOSE: Mortality from head and neck squamous cell carcinoma (HNSCC) is usually associated with locoregional invasion of the tumor into vital organs including the airway. Understanding the signaling mechanisms that abrogate HNSCC invasion may reveal novel therapeutic targets for intervention. The purpose of this study was to investigate the efficacy of combined inhibition of c-Src and PLCγ-1 in the abrogation of head and neck squamous cell carcinoma (HNSCC) invasion. EXPERIMENTAL DESIGN: PLCγ-1 and c-Src inhibition was achieved by a combination of small molecule inhibitors and dominant negative approaches. The effect of inhibition of PLCγ-1 and c-Src on invasion of HNSCC cells was assessed in an in vitro Matrigel coated transwell invasion assay. In addition, the immunoprecipitation reactions and in silico database mining was used to examine the interactions between PLCγ-1 and c-Src. RESULTS: Here we demonstrate that Inhibition of PLCγ-1 or c-Src with the PLC inhibitor U73122 or the Src family inhibitor AZD0530, or using dominant-negative constructs attenuated EGF-stimulated HNSCC invasion. Further, EGF stimulation increased the association between PLCγ-1 and c-Src in HNSCC cells. Combined inhibition of PLCγ-1 and c-Src resulted in further attenuation of HNSCC cell invasion in vitro. CONCLUSIONS: These cumulative results suggest that PLCγ-1 and c-Src activation contribute to HNSCC invasion downstream of EGFR and that targeting these pathways may be a novel strategy to prevent tumor invasion in HNSCC.